Konstruksi Pertimbangan Hakim: Pengakuan Identitas Jenis Kelamin Seorang Transgender Dalam Fase Sintonik - Tan, Winsherly; Rusdiana, Shelvi; Simanjuntak, Elisa Nilla Sari (Faculty of Law, Andalas University, 2023)
The societal stance on transgender individuals elicits various reactions, ranging from acceptance to rejection. This, in turn, has a significant impact on the discriminatory treatment that gender reassignment applicants receive from the community. Generally, individuals who seek gender reassignment do so due to discomfort with their gender identity. As such, transgender individuals strive to assert their right to change their gender. In Indonesia, the legal basis for gender reassignment is not positive, as there is no specific regulation governing gender reassignment. However, Article 56 of Law Number 24 of 2013, which amends Law Number 23 of 2006 concerning Population Administration, indirectly provides an opportunity for transgender individuals to apply for a change in their gender status through a court decision. Essentially, judges cannot dismiss a case due to a lack of legal basis and must instead create laws by exploring the existing laws in society. This is what is referred to as